Establishment of a New Marginal Plaque Index With High Sensitivity for Changes in Oral Hygiene. Issue 12 (1st December 2014) - Deinzer, Renate; Jahns, Stephan; Harnacke, Daniela
Abstract : Background: Although several plaque indices exist, they rarely assess in detail the plaque adjacent to the gingival margin, an area most important for periodontal health. This study aims to develop a new marginal plaque index (MPI) and to assess its validity and treatment sensitivity compared to the internationally accepted Turesky modification of the Quigley and Hein Index (TQHI). Methods: Data from two studies with n = 64 and n = 67 participants, respectively, are reported here. Convergence of MPI with TQHI and concurrent and predictive validity with papillary bleeding index were assessed, as was treatment sensitivity to a treatment of proximal hygiene (study 1) or toothbrushing (study 2), respectively. Results: Convergent validity with TQHI is very good. Concurrent and predictive validity parameters of the MPI are similar to the TQHI. The treatment sensitivity of MPI exceeds TQHI by far. This results in a reduction by >70% of the sample size needed to discover significant treatment effects. As expected, the largest treatment sensitivity was observed for proximal MPI measures in study 1, whereas study 2 showed largest effects for cervical measures. Conclusions: MPI appears to be a valid plaque‐scoring system that assesses plaque at the gingival margin. It responds with high sensitivity to treatments aimed at plaque reduction at the gingival margin. Its treatment sensitivity and capacity to differentiate between proximal and cervical plaque make it a promising tool for periodontal research.